ANALISIS FAKTOR EKOLOGI TUMBUHAN LANGKA ROTAN BEULA Ceratolobus glaucescens Blume DI CAGAR ALAM SUKAWAYANA SUKABUMI JAWA BARAT - Rudi Hermawan; Agus Hikmat; Agus Priyono Kartono (Department of Forest Resources Conservation and Ecotourism - IPB University, 2012)
Indonesian forest possesses a huge number of rare plants species but support of data and information that have supported preservation action was not available optimally. One of rare plant is rotan beula (Ceratolobus galucescens Blume). The aims of this study is to determine the structure, composition, and diversity vegetation which grows at habitat of rotan beula; to know the population condition of rotan beula; and to identify the ecological factors of rotan beula. Data was collected from 7 of circular plot sample. The width of every circular plot was 0.1 ha. The processing and analysis of data was done using Minitab's program version 14. The result showed the condition of rotan beula populations was well, they still grow normally. This conditions was described with young age (446 individuals) is more than the total of Rotan beula in old age (162 individuals). The sustainability of rotan beula population at Sukawayana Natural Reserve (SNR) was being threatened by society activity surround the SNR. The other, the abundance of Rotan beula was affected by density of pole level (n=7; t=7.81; p=0.001) and relative humidity of air (n=7; t=12.10; p=0.000). It can be formulated with regression: rotan beula density = -1155 + 0.154 density of pole + 13.9 relative humidity of air. The R2 value of formulation was 98,53%. Key word: Rare plant, ecological factor, preservation, Ceratolobus galucescens Blume.